Efficient and selective aqueous photocatalytic mono-dehydration of sugar alcohols using functionalized yttrium oxide nanocatalysts. Issue 16 (22nd July 2020) - Yang, Juncheng; Li, Xiaoyong; Cheng, Yu; Fan, Chao; Pan, Cheng; Huang, Benhua; Meng, Xu; Zhang, Junjie; Zheng, Aqun; Ma, Xiaomo; Guo, Lina; Luque, Rafael; et al.
Abstract : The mono-dehydration of sugar alcohols such as d -sorbitol and d -mannitol generates 1, 4-sorbitan and 1, 4-mannitan, respectively, which are relevant platform molecules for the synthesis of detergents and pharmaceuticals. Abstract : The mono-dehydration of sugar alcohols such as d -sorbitol and d -mannitol generates 1, 4-sorbitan and 1, 4-mannitan, respectively, which are relevant platform molecules for the synthesis of detergents and pharmaceuticals. Most reported catalytic systems provided access to di-dehydrated products, while mono-dehydration required special efforts, particularly regarding selectivity and reaction temperature. A series of functionalized yttrium oxides were prepared via sol–gel synthesis in this work, which not only showed an interesting micropipe-like morphology, but also contained functional components. These materials were investigated as photocatalysts in the dehydration of d -sorbitol and d -mannitol, exhibiting high selectivity to mono-dehydration. The effects of solvent, temperature and catalyst were fully discussed. A catalytic mechanism was proposed based on the experimental results and calculations.